A Randomized, Crossover Study on the Effect of Food on the Pharmacokinetic Characteristics of Morphine ARER (MorphaBond™ ER), an Abuse-Deterrent Formulation of Extended-Release Morphine - Kinzler, Eric R. (Adv Ther, 2019)
INTRODUCTION: Food can alter the pharmacokinetics of certain abuse-deterrent formulations. Morphine ARER is an oral abuse-deterrent formulation of ER morphine sulfate tablets formulated with physical and chemical properties that contribute to the abuse-deterrent aspects of the drug. This study compared the relative bioavailability of Morphine ARER in the presence and absence of food. METHODS: This was a randomized, single-dose, two-treatment, crossover study in which healthy adults received Morphine ARER 100 mg under fasting and fed conditions. Subjects were given naltrexone 50 mg to limit opioid effects. Plasma concentrations of morphine and its active metabolite morphine-6-glucuronide (M6G) were obtained up to 48 h post-dose; area under the plasma concentration-time curve (AUC) from time 0 extrapolated to infinity (AUC(0–∞)), maximum observed plasma concentration (C(max)) and time to C(max) (T(max)) were calculated. Safety was evaluated by observation or report of adverse events, which were monitored during the treatment periods. RESULTS: Of 28 enrolled subjects, 27 completed all treatments; 1 subject in the fasted group withdrew voluntarily. Under fed conditions, the C(max) for morphine was 33% higher (44.78 vs. 33.30 ng/ml for fed and fasted conditions, respectively) and the median T(max) was 30 min longer than under fasted conditions. The overall morphine exposure (AUC(0–∞)) was similar for fed (440.6 ng · h/ml) vs. fasted conditions (395.1 ng · h/ml). For M6G, the C(max) and AUC(0–∞) were similar under both conditions, and the median T(max) for M6G was 60 min longer under fed conditions. Common adverse events were somnolence and nausea. CONCLUSION: Morphine ARER can be administered without regard to food. PLAIN LANGUAGE SUMMARY: Plain language summary available for this article. FUNDING: Inspirion Delivery Sciences, LLC.